Unit commitment solution in electrical power using Turbo C++/ Nik Ibrahim Nik Abdullah - Nik Abdullah, Nik Ibrahim (1998)
The objective of this project is to apply Priority List Method as a method solving of Unit Commitment in electrical power system. Fundamental to the economic operating of a power generation unit is heat rate characteristic. Every generator unit operates at different modes and none of the generator has similar heat rate characteristic. Therefore by manipulating this characteristic, Unit Commitment plans the best set of units to be available to supply the forecasted load demand. Turbo c++ will be used to process the data. Functions such as while, if and for are used to search generator or load status and to make decision for Unit Commitment by considering the start up and shut down rules. In this project, turbo c++ will be used to plan the Unit Commitment on actual daily load data from TNB according to Priority List Method.